(untitled) (VETERINARIA, 2025)
This case report describes a foal of the Bosnian Mountain Horse (Equus ferus caballus) type, found in a cachectic and life-threatening condition in Eastern Bosnia, in April 2024. The foal, approximately two months old and orphaned, was adopted by local residents. It was fed a diet based on diluted cow’s milk, forage and concentrates, supplemented with minerals and vitamins. The foal was monitored until it reached one year of age. Morphometric measurements included front cannon girth, thorax girth, body length, height at withers, and height at croup. Despite non-standard feeding and care conditions, the foal showed progressive recovery and development comparable to healthy foals of the same breed.